2017
DOI: 10.1186/s12891-017-1599-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of change of tunnel axis angle on tunnel length during double-bundle ACL reconstruction via the transportal technique

Abstract: Background: Commercially available flexible reamer and curved guide systems allow a certain degree of control over intra-articular tunnel orientation, therefore allows a wide range of intra-osseous femoral tunnel orientations, contrary to the femoral tunneling technique using a straight guide pin, which are determined by knee flexion angle. We sought to find the clinical relevance of intra-osseous femoral tunnel orientations in the respect of tunnel length. To evaluate the relationship between the tunnel axis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
5
1
Order By: Relevance
“…However, in the first study only 18 reconstructions used the flexible system [14] and neither study randomised their patients. This increase is likely due to the additional control that the surgeon has, using the curved guide, to determine tunnel direction seen by Wang et al [35]. A smaller increase, of only 2.8 mm, was shown in the present study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, in the first study only 18 reconstructions used the flexible system [14] and neither study randomised their patients. This increase is likely due to the additional control that the surgeon has, using the curved guide, to determine tunnel direction seen by Wang et al [35]. A smaller increase, of only 2.8 mm, was shown in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…The next limitation is that the use of a curved guide (and flexible wire) means the surgeon has far more control of tunnel direction than when using a rigid wire. Wang et al showed that this can be used to avoid short tunnels [35]. The positioning of the curved guide was not controlled, in the present study, so this cannot be fully accounted for in the results.…”
Section: Discussionmentioning
confidence: 71%
“…Although the outside-in technique, which allows the point of the outlets to be controlled on the femoral lateral surface, may be considered, this technique leads to acute graft bending, which is associated with poor graft maturation. 35 Therefore, for such knees, femoral drilling using the flexible reamer and curved guide system, which allows a certain degree of control over intra-articular tunnel orientation 36 and can produce significantly more anteverted femoral tunnels than those obtained with a rigid drill 37 or other fixation methods such as anchors or staples, may be better.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 However, there is no consensus on the optimal time to perform surgery as some researchers believe that early-stage surgery may increase the activity of knee joints, which is conducive to functional recovery, whereas some believe that in the early stage, considering factors such as edema, blood clots, and inflammatory reactions in the joints, surgery performed at this time may increase the risks of knee joint stiffness and synarthrophysis. 4,5 Wang et al previously compared the degree of synarthrophysis and stability between patients with ACL injury who underwent early-stage (≤3 weeks) and advanced-stage (>3 weeks) surgery, and the results demonstrated that autologous ligament grafting at the early stage could effectively restore joint stability without increasing the degree of synarthrophysis. 6 In this regard, we selected 3 weeks as the threshold between early-stage and advanced-stage surgery and retrospectively analyzed the clinical data of patients with ACL injury who underwent reconstruction with autologous ligament grafting and compared the effects of early-stage (≤3 weeks) and advanced-stage (>3 weeks) surgery on their knee joint functions, activity, stability, and QOL to determine the optimal time to perform ACL reconstruction with autologous ligament grafting.…”
Section: Introductionmentioning
confidence: 99%
“…Reconstruction with autologous ligament grafting is considered the principal treatment method for ACL injury; it can effectively restore the stability of knee joints, promote functional recovery, and improve patients' QOL 2,3 . However, there is no consensus on the optimal time to perform surgery as some researchers believe that early‐stage surgery may increase the activity of knee joints, which is conducive to functional recovery, whereas some believe that in the early stage, considering factors such as edema, blood clots, and inflammatory reactions in the joints, surgery performed at this time may increase the risks of knee joint stiffness and synarthrophysis 4,5 . Wang et al previously compared the degree of synarthrophysis and stability between patients with ACL injury who underwent early‐stage (≤3 weeks) and advanced‐stage (>3 weeks) surgery, and the results demonstrated that autologous ligament grafting at the early stage could effectively restore joint stability without increasing the degree of synarthrophysis 6 .…”
Section: Introductionmentioning
confidence: 99%